Determination of CTOD and CMOD of tubular T-joint using the finite element software - COSMOS/M - 203511 Ooi, Seok Teng (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005